Aluminothermic production of silicon using different raw materials - K Jakovljevic; N Simkhada; M Zhu; M Wallin; G Tranell (The Australasian Institute of Mining and Metallurgy, 2024)
Silicon is a vital element in many products today, such as electronic components, solar devices, high-quality alloys, and many others. The growing global demand highlights the need for the development of sustainable production methods to meet this demand as an alternative to the current carbothermic reduction, submerged arc furnace (SAF) based process. An alternative to this is the aluminothermic reduction of quartz in a CaO-SiO2 slag, which not only reduces direct carbon dioxide emissions but also promotes the utilisation of secondary raw materials such as quartz fines, aluminium dross and scrap as well as secondary alumina (SA) from dross recycling. In the current study, the effects of SA and CaF2 additions to slag on the resulting metal composition and metal yield were explored. Results were compared with thermodynamic simulations using FactSage™ 8.1. Experimental results show that, in agreement with thermodynamic simulations, the silicon content of the alloy is increased, while the Ca is decreased for starting slags where CaO-SiO2 is partly replaced by CaF2. Similarly, the addition of SA to the initial slag results in an alloy with a higher silicon content.